Do you remember being told what happened to grandma? The role of early socialization on later coping with death - Martinčeková, Lucia (Death Stud, 2018)
Using a mixed-methods approach, we examined how participants’ memories of socialization regarding death might influence their self-reported coping with losses in childhood and adulthood. We recruited 318 adults to complete an online survey. Path analyses indicated that participants who remembered their parents shielding them less from issues related to death reported better coping as children and adults. Qualitative responses suggested participants wanted to receive more information about death from their parents as they went through the grieving process. We highlight the potential benefits of socializing children about death, and how it may aid in their coping with death-related events.